Artistic Creation as a Mystical Transmutation in Virginia Woolf’s To the Lighthouse - Salah BOUREGBI (Annals of Philosophy, Social and Human Disciplines, 2017)
This paper deals with the mystical experiences in Virginia Woolf’s artistic creation. Woolf denies any form of modernism that cannot transcend reality. There are moments, where reality is never what it is but a vision — a perspective — whose meaning is beyond the graspable. Reality, thus, becomes un-reality — a halo, and the artist becomes a contemplator — a devotee to such visionary manifestation. Virginia Woolf does not make an exception to this rule. She is par excellence a mystic. The artistic design of her novels, mainly, To the Lighthouse, is of transcendental dimension. Both, Mrs Ramsay’s and Lily Briscoe’s perceptions of life are beyond the palpable: their selves merge within a process of sublimation comparable to that of mysticism. In other words, art (mainly fiction) becomes a process of change from the factual to the transmutable.